Model Pembelajaran Alquran Dalam Membentuk Muslim Hamilil Qur’an Lafdhan Wa Ma’nan Wa ‘Amalan: (Studi Kasus Di Pondok Pesantren Madrasatul Quran Tebuireng Jombang) - Lusmiyatun Nisa; Hanifuddin Hanifuddin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Islamic boarding schools based on the Koran have different learning models because it is a characteristic and it can affect the results of learning the Koran itself. The Madrasatul Qur'an Islamic boarding school Tebuireng Jombang has a Qur'anic learning model that is applied in three educational units in the pesantren, namely: the tahfidz unit, the school unit, and the majlis tarbiyah wa at ta'lim unit. The goal is that students not only memorize the Koran in lafadh, but can understand its meaning and be able to practice the teachings of the Koran itself. Based on the above background, the problems/focuses in this study are: 1) Al-Quran Learning Model in the tahfidh unit in the field of lafdhan 2) Al-Quran Learning Model in the ma'nan school unit 3) Al-Quran Learning Model in the majlis tarbiyah wa at ta' unit lim field of 'practice. This study states that the learning model of the Qur'an in the tahfidh unit in the field of lafdhan with qiraah muwahhadah, namely: classical fashahah, mudarasah, deposit and tasmi' so that students memorize 30 juz with qiraah muwahhadah standards and master the science of qiraah sab'ah. School units in the field of ma'nan with the bandongan model, namely: Classical, and general/halaqah stadiums so that students are able to understand and explore the contents of the Koran in terms of ma'nan. The majlis tarbiyah wa at-ta'lim unit in the field of 'practice through example', namely: ubudiyah habituation, and moral development karimah so that students have skills in developing talents, and are able to organize.